Making Humanoid Robots More Acceptable Based on the Study of Robot Characters in Animation - Fatemeh Maleki; Zeinab Farhoudi (IAES International Journal of Robotics and Automation (IJRA), 2015)
In this paper we take an approach in Humanoid Robots are not considered as robots who resembles human beings in a realistic way of appearance and act but as robots who act and react like human that make them more believable by people. Regarding this approach we will study robot characters in animation movies and discuss what makes some of them to be accepted just like a moving body and what makes some other robot characters to be believable as a living human. The goal of this paper is to create a rule set that describes friendly, socially acceptable, kind, cute... robots and in this study we will review example robots in popular animated movies. The extracted rules and features can be used for making real robots more acceptable.